OPINIONS OF EIGHT GRADE STUDENTS ON THE GLOBAL PROBLEMS - Canan AKYOL; Osman SABANCI; Melike FAİZ (International Journal of Eurasia Social Sciences, 2017)
After the Industrial Revolution, world passed through a fast mechanization process. This process continued with technological developments. Using the sources presented by the earth by people unlimitedly has caused that economic, environmental, social problems and safety problems, crossing lines, are encountered with. The mentioned problems exceeded the sizes which the countries can solve and gained a global characteristic with respect to their causes and effects. The natural problems arisen from the structure of the Earth, climate, hydrography, soil, plant cover, and zoo-geography characteristics; people problems related with population and settlement; the economic problems related with agriculture, husbandry, mining, energy resources, industry, communication, transportation, tourism, and commerce increasingly continue. The global problems are closely related with all of the areas of learning of the social studies course. Furthermore, these problems may not be considered separated with the social studies course, educating the efficient citizens of the future, with respect to effecting the generations of today and future. In this research it is targeted to reveal the opinions of the eight grade students on the global problems. The study is designed in the qualitative research pattern. The research data was collected through structured interviews from the students. The structured interview form consists of the personal information and the interview questions related with the global problems. The study group of the research consists of 149 eight grade students. When determining the study group, the students were selected from seven regions of Turkey for increasing the participant diversity. After the data was analyzed through descriptive analysis, the themes were determined. According to the results of the study, it was determined that the most important global problem is the problems related with population and the problems arisen from the climate characteristics. The global problem, seen as the most important in Turkey, is the problems related with settlement and problems arisen from the climate characteristics. Considering in general, the global problem, repeated by the students least, is the problems caused by economy. Even though most of the students states that there is a relationship between the global problems and social studies course, the number of the ones stated that this relation does not exist is considerable.